Chemosensitizing effect of maitake mushroom extract on carmustine cytotoxicity in human bladder cancer cells - Hillelsohn, Joel; Stern, Michael; Iskander, Mina; Choudhury, Muhammad; Konno, Sensuke (International Journal of Research in Medical Sciences, 2020)
Background: Despite several therapeutic options available for bladder cancer, the outcomes are less satisfactory. To find a more effective modality, we were interested in the bioactive mushroom extract, PDF, which has been shown to sensitize certain anticancer drugs. Accordingly, we investigated if cytotoxic effects of several anticancer drugs used on bladder cancer patients could be enhanced with PDF in vitro. Methods: Human bladder cancer T24 cells were treated with four anticancer drugs, carmustine (BCNU), 5-fluorouracil (5FU), cisplatin (CPL), and doxorubicin (DOX) alone, their combinations, or in combination with PDF, and cell viability was determined. To explore the anticancer mechanism, the status of glyoxalase I (Gly-I), an enzyme involved in the drug resistance of cancer cells, and oxidative stress that can cause severe cellular injury/damage was also assessed. Results: BCNU and 5FU alone resulted in a >50% reduction in cell viability but CPL and DOX had no such effects. Only a combination of BCNU and PDF led to a drastic ( 90%) cell viability reduction, accompanied by inactivation of Gly-I and an increase in oxidative stress. However, any combinations of other drugs and PDF had little effects on cell viability, Gly-I activity, or severity of oxidative stress. Conclusions: This study shows that anticancer activity of BCNU is significantly potentiated with PDF in T24 cells. This is rather attributed to inactivated Gly-I and increased oxidative stress. Therefore, PDF appears to have a chemosensitizing effect capable of enhancing BCNU cytotoxicity, which may offer an alternative, improved therapeutic option for bladder cancer.